Drug reaction with eosinophilia and systemic symptoms: is cutaneous phenotype a prognostic marker for outcome? A review of clinicopathological features of 27 cases. (30th January 2013) - Walsh, S.; Diaz‐Cano, S.; Higgins, E.; Morris‐Jones, R.; Bashir, S.; Bernal, W.; Creamer, D.
<x xml:space="preserve">Abstract</x> Summary Background Drug reaction with eosinophilia and systemic symptoms (DRESS) describes a heterogeneous group of severe adverse reactions to medications. The cutaneous phenotype has a number of guises, accompanied by a variety of systemic features including fever, haematological abnormalities and visceral involvement, most commonly the liver. Clinical markers of prognosis have not been identified. Objectives To assess the cutaneous signs and dermatopathological features of DRESS in order to identify potential prognostic markers. Methods We reviewed the clinical features, dermatopathology and outcomes of 27 consecutive cases of DRESS presenting to a single unit. Results Four distinct patterns of cutaneous involvement were identified: an urticated papular exanthem (13/27 patients), a morbilliform erythema (three of 27), an exfoliative erythroderma (three of 27) and an erythema multiforme‐like (EM‐like) reaction consisting of atypical targets (eight of 27). All patients mounted a fever, most developed lymphadenopathy (24/27) and peripheral eosinophilia (25/27) and the most common organ involved was the liver (27/27). Review of the dermatopathic features of patients with DRESS demonstrated a superficial spongiotic dermatitis in the majority of cases (16/27). A smaller number of cases showed basal cell vacuolar degeneration and necrotic keratinocytes (nine of 27). The patients with these biopsy findings more commonly had an EM‐like cutaneous phenotype, and more severe hepatic involvement. Three patients died, two following failed liver transplants. Conclusions Our series is the first in which a detailed dermatological assessment has been made of consecutive patients presenting with DRESS, and the largest U.K. series to date. Our results suggest a possible prognostic role of the cutaneous and dermatopathic findings in DRESS in predicting the severity of visceral involvement in this syndrome. What's already known about this topic? Drug reaction with eosinophilia and systemic symptoms (DRESS) has a heterogeneous clinical presentation, with a skin eruption of variable morphology. DRESS carries considerable morbidity and mortality, usually hepatic in origin, although renal, pulmonary and pericardial involvement can be seen. What does this study add? The cutaneous phenotype in DRESS can be categorized as an urticated papular exanthem, a morbilliform erythema, exfoliative erythroderma or erythema multiforme‐like (EM‐like). An EM‐like eruption DRESS may be prognostic of more severe hepatic involvement.